PROFIL SUBJECTIVE WELL BEING MAHASISWA DENGAN ORANG TUA TUNGGAL - Putra, Rama Andika; Suryadi, Suryadi; Wae, Rahmawati (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2025)
This research is motivated by students' dissatisfaction with life, such as feeling that the life they are living is meaningless, feeling embarrassed because their parents died, there are some students who hate their parents because they think they no longer love them. The aim of the research This is to describe: 1) Subjective wellbeing of students with single parents’ terms of pleasant affect 2). Subjective wellbeing of students with single parents of unpleasant affect 3). subjective wellbeing of students with single parents’ terms of Life satisfaction. This research uses quantitative descriptive methods. The population of this study was guidance and counseling students, totaling 30 students. This sampling technique was carried out using a purposive sampling technique, namely 30 people. The data collection technique used was a questionnaire instrument and the data analysis technique used was descriptive analysis. The results of this research show that the subjective well-being profile of students with single parents is in the quite high category, 1). From the pleasant affect indicator, students are in the high category, 2). From the unpleasant affect indicator, students are in the quite high category. 3). From the Life Satisfaction indicator, students are in the quite high category. From the research results, students can further improve Subjective well-being from the moderately high category to the high category by increasing pleasant affect or referring to students' beliefs about their well-being or happiness in living their lives. Based on the research results, it is recommended for students with single parents to achieve subjective well-being so that it has an impact on life satisfaction